Rehabilitation of women after conservative and surgical treatment - R. S. Moldassarina; G. K. Manabayeva; Z. Ye. Akylzhanova; A. M. Rashidova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The relevance of the study is due to the increase in the volume of conservative and surgical care for women who need mandatory rehabilitation measures in the postoperative period. Until relatively recently, there were very few rehabilitation facilities in the country where women could recover under the supervision of a nurse. Therefore, rehabilitation could drag on for many months and it was very difficult to fully return to normal life. In the modern world, it has become possible to undergo all the necessary analyzes and conduct treatment using the latest scientific methods on high-precision equipment, and then perform a full course of postoperative regeneration. After all, medical centers have great technological capabilities today and control the healing process as soon as possible. The nature of the measures for the recovery of women depends on the changes in the body, which are due to the individual background at the time of treatment. It is important to understand the dependence of a woman's position at the time of recovery: the duration of taking medications, the presence of psychological trauma, the development of chronic diseases, the frequency of repeated interventions. The aim of the study is a step-by-step volumetric study of the implementation of various measures aimed at the rehabilitation of women after conservative and surgical treatment. Modern approaches require responsibility, high qualifications of medical personnel and the direct participation of the patient himself in this process. Timely start of rehabilitation ensures productive restoration of lost functions. The main principle of success is the use of standardized methods, informing the patient at all stages of treatment, using techniques with minimal consequences and maximum impact, and analyzing the course of the postoperative period. The need for an in-depth study of the features of providing medical care to patients with gynecological diseases, including after surgical interventions, is confirmed. The practical significance of the material lies in the high-quality and effective organization of medical rehabilitation, which is of key importance for the full restoration of the functions of the woman's reproductive system.